The Impact of Learning Experiences on Meeting Teacher Accreditation Standards: A Mixed-Methods Study - Yuan, Peili; Chen, Yuze (Pacific International Journal, 2024)
Professional Accreditation for teacher education programs is a quality assurance measure for normal universities. To clarify the factors affecting student teachers’ learning and their mechanisms, a mixed-methods study was conducted on government-funded student teachers. The study found that learning experiences in areas such as clear goals, student support, appropriate assessment, teaching quality, and course organisation have varying degrees of influence on learning outcomes. The mechanisms of influence include: the combined effect of misaligned learning goals and simplified exam content hinders the improvement of learning quality; gaps in subject systems and structural shortages of teacher resources undermine the distinctive features of teacher education; and an imbalance between increasing learning challenges and insufficient student support obstructs the development of professional competencies. Therefore, universities should leverage participation in professional accreditation as an opportunity to reform teacher education curricula, build high-quality teaching teams, optimize the structure of teacher resources, and improve student support services to create an excellent training environment